The state of New Testament studies : a survey of recent research - Scot McKnight; Nijay K. Gupta (Grand Rapids, Michigan : Baker Academic a division of Baker Publishing Group, 2019)
"In twenty-three chapters, the contributors to this book, all experts in their respective fields, survey the state of academic discussion with respect to their text or topic. Each chapter breaks the conversations into a few key headings with guidance on the most important contributions, controversies, and questions. At the end of each chapter you will find a set of reflections that sum up in brief the 'state of New Testament studies' today."--Preface, page 5
Keywords: Bible. New Testament; Bible. New Testament Criticism, Textual History 21st century